TINJAUAN YURIDIS TEMBAK MATI DITEMPAT OLEH BADAN NARKOTIKA NASIONAL REPUBLIK INDONESIA TERHADAP PELAKU PENGEDAR NARKOTIKA - Irham Parlin Lubis; Syafruddin Kalo; M. Hamdan; Mahmud Mulyadi (Universitas Quality, 2021)
The misuse and illegal circulation of narcotics of the government has been assertive bygiving sanctions in the form of death penalty for the drug city, it does not make the othertowns deterrent, the worse drug circulation is precisely controlled from the prisoner byinmates. It is thus necessary a decisive action in stopping narcotic circulation. One of thedecisive actions of the National Narcotics Agency by shooting dead in a drug town tryingto fight. But in the eradication of narcotics criminal offence conducted by the NationalNarcotics Agency by firing death in place against suspected narcotics dealers accordingto the authors has occurred violations of the procedure and also violations of rightsHuman. Firing action is at its destination just to paralyze the perpetrator, even beforefiring towards the perpetrator of law enforcement officials give warning first, in case ofwarning the shot is not obeyed, the direct firing is directed at the limbs that do not harmthe soul. In principle any person accused of committing a criminal offense has the rightsto be protected such as the right to gain a sense of security, the right to the presumptionof innocent access, the right to obtain fair and equal treatment in the face of the law andthe right to defend themselves before the law.